“Playing helps you feel at home”: recovery and reintegration of child victims of political and social violence - Głos, Aleksandra; Martín Corredor, Lina; Vargas Celis, Ivonne; Monreal, Verónica; Valenzuela Sarrazin, Antonia (Frontiers in Psychology, 2025)
IntroductionPlay is a fundamental right of every child and one of their most important needs. However, despite the countless benefits of play for children's wellbeing and development, it is often overlooked in public policies, and especially so in the situation of political conflict and social unrest.MethodsDrawing from the children's rights framework, this qualitative study explores the role of play for the psychological recovery and social reintegration of children affected by political and social violence. It does so within the wider framework of peace studies and includes the exploration of children's conceptions of peace and the question of how play can contribute to promoting a culture of peace in violence-stricken societies. Through play-based focus groups with child migrants and refugees in Chile, we explored their own views on the therapeutic and peace-building potential of play as a response to self-reported problems.ResultsThe children in our study told a dual story: a story of trauma and violence, and another one about hope, friendship, and resilience, all of which were greatly facilitated by play.ConclusionFor that reason, as representatives of children's vulnerable voices, we advocate for the greater and more systematic provision of children's right to play in conflict zones and its inclusion in peace-building programs.